Perbandingan Sistem Peramalan Penjualan Dengan Metode Exponential Smoothing Dan Single Moving Averages Menggunakan Uji Statistik - Arum Nawang Sari; I Gede Arya Utama; Weny Endah Kusumawardhani (Jurnal Sistem Informasi Universitas Dinamika, 2012)
PT. Surya Prima Perkasa is a big medicine distributor company which is spread all over Indonesia. Sales as a team that handles the sales transaction data of medicines have not done well and still use excel to record the transaction. Sales transaction data will be used Parts Sales to determine how many medicine orders for the next periods. However, these sales estimates sometimes have quite a big difference from the actual sales numbers, since the prediction does not use a certain formula and do not take into account sales forecasting errors.Application of sales forecasting with Exponential Smoothing and Single Moving Averages method are applications that can help PT. Prima Surya Perkasa to determine the number of total sales in the next periods. Exponential Smoothing forecasting methods will take into account average (smoothing) the data of the past exponentially by repeating calculations continuously using the latest data. Single Moving Averages are used to forecast the next periods, as well as cope with the trend better.In this application, Exponential Smoothing and Single Moving Averages methods are used to predict the amount sales for the next periods. Then the results from both methods were compared using statistical tests, where the accepted method is feasible for use forecasting.To determine the quality of orders in the future using the Economic Order Quantity (EOQ). Based on trial results that have been done can be concluded that the application is made to provide information to support decisionof Managerin determining the amount of medicine ordering. Keyword :Sales Forcasting, Exponential Smoothing, Single Moving Averages, Statistical testing.